2020
DOI: 10.1163/22244662-20191058
|View full text |Cite
|
Sign up to set email alerts
|

Antlions in interaction: confrontation of two competitors in limited space

Abstract: The study focused on the behaviour of sit-and-wait antlion larvae in interspecific interactions. Antlion larvae usually occur in clusters with a high density of individuals; therefore, competition can be intense. We observed two abundant antlion species, E. nostras and M. formicarius, which co-occur in some habitats. In a simple habitat choice experiment where substrates differed according to sand particle size, we found that E. nostras exhibited dominance over M. formicarius. Most E. nostras larvae remained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The question is whether one species is more competitive, which may be a behavioural trait (Klokočovnik et al, 2020), or whether the species have different habitat requirements. In habitats where the species occur separately, E. nostras always resides in protected microhabitats, while M. formicarius inhabits open, more exposed areas, usually in forests (Badano & Pantaleoni, 2014; Devetak & Arnett, 2015; Tusun & Bozdoğan, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question is whether one species is more competitive, which may be a behavioural trait (Klokočovnik et al, 2020), or whether the species have different habitat requirements. In habitats where the species occur separately, E. nostras always resides in protected microhabitats, while M. formicarius inhabits open, more exposed areas, usually in forests (Badano & Pantaleoni, 2014; Devetak & Arnett, 2015; Tusun & Bozdoğan, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of whether E. nostras is more adapted to interactions or must therefore be a stronger competitor to secure space for trap construction but is more influenced by abiotic factors, in contrast to M. formicarius . Klokočovnik et al (2020) found that interactions between E. nostras and M. formicarius exerted a stronger influence on latter species. In a habitat where both species co‐occur, E. nostras occupies more favourable sites, which is likely the result of partitioning that allows the species to coexist (Adar et al, 2016; Griffiths, 1992; Polis, 1981; Schoener, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…This process, termed “shadow competition”, assumes that sites in the periphery of the TB predators' cluster receive more prey than sites in the center 42 44 . Finally, many TB predators, especially spiders and antlions, prey on whatever prey is caught in their trap, including related species and conspecifics 45 48 . The outcome of such cannibalistic and intra-guild predation attempts strongly depends on body size (larger individuals prey on smaller ones 22 , 49 , 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…Antlions are semi‐sessile predators and exhibit strong site fidelity because pit relocation is energetically costly (Crowley & Linton, 1999; Lucas, 1985). Hence, interactions among nearby larvae are common during pit building and maintenance (Gotelli, 1997; Devetak, 2000; Klokocovnik et al, 2020; Ovadia, Scharf, Barkae, Levi, & Alcalay, 2020). For example, co‐occurring antlion species can compete for space, showing dominance hierarchies according to sand particle size (Klokocovnik et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, interactions among nearby larvae are common during pit building and maintenance (Gotelli, 1997; Devetak, 2000; Klokocovnik et al, 2020; Ovadia, Scharf, Barkae, Levi, & Alcalay, 2020). For example, co‐occurring antlion species can compete for space, showing dominance hierarchies according to sand particle size (Klokocovnik et al 2020). Moreover, antlion larvae of different species can directly compete among them through intra‐guild predation (Ovadia et al., 2020).…”
Section: Introductionmentioning
confidence: 99%